NEUROTROPIC ACTIVITY OF PLANT ALKALOIDS (Experimental biology, 2021)
Natural alkaloids are promising compounds for the development of new domestic neurotropic drugs based on them. The article presents the results of a study of the neurotropic effect of plant alkaloids (harmine, delphinifolin, echinopsin, zongoramine). The assessment of the neurotropic effect of the samples of alkaloids was carried out on the model of experimental stress using the tests «Open field» and «Raised cross-shaped maze».. As a result of the conducted studies, it was found that samples of plant alkaloids delphinifolin, harmine, echinopsin and zongoramin at a dose of 10 mg / kg exhibit a neurotropic effect, increasing the level of research activity, reducing the level of anxiety, fear and anxiety in animals in the tests «Open Field» and «Raised cross-shaped maze». The presence of an aryl group in the molecules of harmine, delphinifolin, zongoramine, and echinopsin is important for their neurotropic activity.
Keywords: alkaloids, harmine, delphinifolin, echinopsin, zongoramine, neurotropic effect, experimental model